DESIGNING A PROJECT OF USING LEARNER- CENTEREDNESS IN TEACHING ENGLISH AT SENIOR HIGH SCHOOLS IN MANOKWARI - Sukristiningsih, Sukristiningsih; Saragih, Yansen M.I. (Universitas Papua, 2016)
Special Autonomy Law (UU OTSUS Provinsi Papua) Chapter XV; article 52, verse 2, confides the implementing of English as a second language in Papua (West Papua province and Papua province). However, some complexities are faced to implement English as a second language in Papua. The complexities are; the difficulty in teaching English at school, lack of motivation to study English by student, different level of studentâs English competence, and lack of good English teacher. This article aims to give contribution to solve the complexities above, especially in English teaching- learning process at senior high school level in Manokwari regency, west Papua province. The concept offered to solve the problems in teaching â learning English process is by using Student Centered Learning (SCL) concept. This concept is recommended by experts and suitable to be applied in senior high school level. There are some steps to implement SCL concept, they are; designing the project, implementing the design and evaluating the project. By implementing SCL concept, the teaching- learning English process in senior high school in Manokwari regency is expected to be useful for students and English teachers.